Conceptualising healthy and sustainable diets: a policy coherence analysis - Mazzocchi, Giampiero; Angeloni, Annalisa; Scalvedi, Maria Luisa; Henke, Roberto; Giuca, Sabrina; Borsotto, Patrizia (Frontiers in Sustainable Food Systems, 2025)
In the last decade, crises and profound changes in the socio-techno-economic systems have questioned the definition and conceptual frameworks of Healthy and Sustainable Diets (HSDs). A growing number of institutional documents, government agencies and high-level organisations are addressing the (re)definition of HSDs, and the multiple factors that favour or hinder the creation of food systems that balance healthy nutritional habits with fair, ecologically correct, and socially acceptable food supply mechanisms. Such work has spotlighted a relevant issue of policy coherence and advocated for a higher level of policy integration in favour of HSDs. Within this streamline, the paper focuses on building up an advanced and improved conceptual framework to orient policies supporting the promotion of HSDs within the context of national food policies. Moving from the theoretical background around HSDs and the most widely recognised common definitions, this study has identified and discussed the major policy domains addressing the implementation of HSDs. To this aim, we have analysed the documents which focus on HSDs at International, European and National (Italian) level and checked the relevance of policy domains that aim to the promotion of HSDs. Our results show that International documentation provides the definitional framework, objectives, and enabling conditions for achieving sustainable food systems, whilst the European institutions and organisations are focused on the trade-offs that arise between the socioeconomic dimensions of food and nutrition within sustainable food systems. At the National level, Italian policies on HSDs are very much anchored to the nutritional and health dimensions and food consumption behaviours. They have elements of connection with food processing but are poorly connected with agricultural components and productive aspects of food systems, as well as those linked to socio-economic aspects.